The effectiveness of using a module on the benefits of moringa leaves to increase knowledge of hiv/aids patients in improving the immune system - Marlina, Lina; Priandini, Sisca; Farozi (Journal of Midwifery and Nursing, 2024)
The increase in HIV cases in West Java is ranked 2nd out of the 5 largest provinces with HIV in Indonesia with 1,224 people and 223 cases in Bekasi Regency in 2021. In the case of HIV sufferers, it is certain that HIV treatment will require a lot of money, so other alternative treatments are needed to overcome this. Moringa leaves (Moringa oleifera) are widely used and trusted as a medicine for infections, anti-bacterial, urinary tract infections, external wounds, anti-hypersensitivity, anti-anemic, diabetes, colitis, diarrhea, dysentery and rheumatism. This research used a quantitative research design with a quasi-experimental approach with one group with pre & post test, where the researcher carried out treatment on respondents, namely in the form of measuring knowledge before and after giving a module about the benefits of Moringa leaves in improving the immune system in HIV/AIDS sufferers in the district area. Bekasi. The average pre test score is 7.40, the minimum score is 5 and the maximum score is 9. The average post test score is 8.23, the minimum score is 5 and the maximum score is 10. Of the 30 respondents the average pre test score is 7.40 and The average post test score is 8.2. The results of the statistical test showed a p value of: 0.005 (p< ?: 0.05), meaning that there was an effect of using the module in increasing the knowledge of HIV/AIDS sufferers about the benefits of Moringa leaves in improving the immune system